Resting metabolic rate analysis in chronic hemiparesis patients - Mauricio de Sant'Anna Jr; Leonardo Coelho Eboli; Julio Guilherme Silva; Alan Gomes dos Santos; Michele Lourenco; Adalgiza Mafra Moreno; Gabriel Rodriguez de Freitas; Marco Orsini (MDPI AG, 2014)
The objective of the present study was to compare resting metabolic rate (RMR) of chronic hemiparetic patients to sedentary health individuals. The sample was composed of 16 individuals, that were divided into two groups. The first group had eight hemiparetic patients and the second group was formed by eight sedentary individuals. To access and analyze the gases information a VO2000 analyzer was used. The following variables were measured: VO2, VCO2, VE, QR, grams of fat (GrFAT), grams of carbohydrate. RMR was calculated based on Weir's equation. There was a significant shift on ventilation variables: VE (P<0.0003), VO2 (P<0.0004) and VCO2 (P<0.0001) on hemiparetic individuals group when compared to control group. When the energetic substrate used behavior is observed, it shows that fat consumption (represented by GrFAT) is higher on the hemiparetic group when compared to controls (P<0.0001) significant differences were observed for RMR between groups (P<0.0001). RMR showed a correlation to VO2 on the hemiparetic group (r=0.9277, P=0.0022). To sum up, it was observed through the results that individuals with hemiparesis as a sequel of stroke showed a RMR larger than normal individuals.